2011
DOI: 10.1016/j.jcf.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lung diffusing capacity for nitric oxide and alveolar-capillary membrane conductance results in oxygen desaturation during exercise in patients with cystic fibrosis

Abstract: These results suggest a limitation in exercise-mediated increases in membrane conductance in CF which may contribute to a drop in SaO(2) and that resting DLNO can account for a large portion of the variability in SaO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 53 publications
6
39
1
2
Order By: Relevance
“…While DL CO can be influenced by both D M and V C , DL NO is thought to be a surrogate of DM, given the affinity of hemoglobin for NO. Similar to previous studies, we have demonstrated an increase in both DL CO and DL NO with exercise in both groups (Hsia, 2002; Tamhane et al, 2001; Wheatley et al, 2011a; Wheatley et al, 2011b). We found that the AA group (which has previously been shown to have reduced ENaC activity) had a greater percent increase in DL CO , DL NO , and DL CO /VA with exercise (endogenous β 2 -adrenergic stimulation) as compared to the AT/TT group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While DL CO can be influenced by both D M and V C , DL NO is thought to be a surrogate of DM, given the affinity of hemoglobin for NO. Similar to previous studies, we have demonstrated an increase in both DL CO and DL NO with exercise in both groups (Hsia, 2002; Tamhane et al, 2001; Wheatley et al, 2011a; Wheatley et al, 2011b). We found that the AA group (which has previously been shown to have reduced ENaC activity) had a greater percent increase in DL CO , DL NO , and DL CO /VA with exercise (endogenous β 2 -adrenergic stimulation) as compared to the AT/TT group.…”
Section: Discussionsupporting
confidence: 91%
“…DL CO , DL NO , and Q̇ were measured in an upright and seated position using the rebreathe technique, with gases sampled by a mass spectrometer (Perkin Elmer MGA-1100, Wesley, MA) and NO analyzer (Seivers Instruments, Boulder, CO) integrated with custom analysis software, as described previously(Snyder et al, 2006b; Snyder et al, 2005; Wheatley et al, 2011a; Wheatley et al, 2011b). Subjects breathed into a five-liter rebreathe bag containing 0.7% acetylene, 9% helium, 0.3% carbon monoxide (C 18 O), 40 PPM NO, and 35% O 2 with a respiratory rate controlled at 32 breaths per minute via metronome.…”
Section: Methodsmentioning
confidence: 99%
“…The first visit was a screening visit where baseline spirometry and a maximal exercise test were performed. The findings regarding the CF patients’ responses to exercise in comparison to healthy subjects has been described previously 25. On the second visit, subjects completed baseline measurements of pulmonary function, diffusion of the lungs for carbon monoxide and nitric oxide (DLCO/DLNO), and a 25-minute EBC collection.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the baseline and 30-, 60-, 90-minutes post-nebulization EBC collections with measures of the diffusion capacity of the lungs for carbon monoxide and nitric oxide (DLCO/DLNO) using a rebreathing technique described previously 2932. Briefly, a 5-liter anesthesia bag was filled with 1575 mL of gas containing 0.7% acetylene, 9% helium 9% He, 0.3% carbon monoxide (C 18 O), 35% O 2 and 40 PPM NO (diluted immediately before the test in the bag from an 800 PPM gas mixture).…”
Section: Methodsmentioning
confidence: 99%
“…This difference is increased during exercise. Peak SaO 2 , during exercise, is related to D L NO [ 20 ]. • Fontan patients ( n = 87) and healthy controls ( n = 9).…”
Section: Selected Findingsmentioning
confidence: 99%